Meta-analysis of FOXP3 gene rs3761548 and rs2232365 polymorphism and multiple sclerosis susceptibility. Issue 38 (September 2019) - Zhang, Yijian; Zhang, Junxin; Liu, Hao; He, Fan; Chen, Angela; Yang, Huilin; Pi, Bin
Abstract: Background: Multiple sclerosis (MS) is a common autoimmune disease of the central nervous system (CNS), and is associated with genetic factors. FOXP3 gene polymorphism has been reported as the risk factor for MS, however, previous studies have showed conflicting results. The purpose of this study is to investigate the association between FOXP3 gene polymorphism and the susceptibility to MS. Methods: Pubmed, Embase, library of Cochrane, and Web of Science were used to search the eligible articles from January 1980 up to October 2018. The odds ratio (ORs) and its 95% confidence intervals (CI) were used to evaluate the strength of association. Allele model, homozygote model, heterozygote model, dominant model, and recessive model were used to evaluate the association between FOXP3 gene polymorphism and MS. Results: A total of 5 studies contained 1276 MS patients and 1447 controls (for rs3761548) and 600 MS patients and 640 controls (for rs2232365) were enrolled in this meta-analysis. The association showed significant differences in allele and dominant model for rs3761548 polymorphism. In addition, a clear tendency to significance was detected in homozygote and recessive model for rs3761548 ( P = .052). Subgroup analysis indicated a significant risk of MS in all genotype models but heterozygotes in Asians. Conclusion: FOXP3 gene polymorphism rs3761548 was associated with a higher MS risk, especially in Asians. This conclusion needs to be validated in more large samples and multiracial studies. Level of evidence: Level III diagnostic study.